The APROVE (Anti-coagulation/platelet treatment in pancreatic resections involving vascular reconstruction) study: results from a worldwide survey - Marchetti, Alessio; Garnier, Jonathan; Habib, Joseph R.; Rompen, Ingmar F.; Andel, Paul C. M.; Salinas, Camila Hidalgo; Ratner, Molly; De Pastena, Matteo; Salvia, Roberto; Hewitt, D. Brock; Morgan, Katherine; Kluger, Michael D.; et al. (Annals of surgical oncology, 2025)
Background: Antithrombotic therapy (AT) aims to strike a balance between preventing thromboembolic and hemorrhagic complications. However, evidence for AT management after pancreatectomy with vascular reconstruction is lacking. We aimed to provide an overview of the current use of AT for pancreatic surgery with vascular reconstructions. Patients and Methods: A web-based survey was distributed to 123 surgeons from high-volume pancreas centers (>50 pancreatic resections/year). AT management after different types of vascular reconstruction were investigated. An “aggressive” protocol was defined as the use of any AT protocol other than prophylactic heparin, aspirin, or their combination. Results: The survey was completed by 80 surgeons (59% Europe, 30% USA, 11% Asia). In Europe/Asia, prophylactic heparin was the most commonly reported protocol after partial venous resection/end-to-end anastomosis/human graft (71%/65%/50%, respectively), and an “aggressive” protocol (86%) was the most frequently used after prosthetic graft reconstruction. Conversely, in the USA, prophylactic heparin + aspirin was the most commonly reported protocol after all types of venous reconstruction. Following arterial reconstruction, heparin + aspirin was the most commonly reported protocol, regardless of region. An “aggressive” protocol was more frequently used in Europe/Asia (odds ratio (OR) 1.28; p < 0.001) and following vein reconstruction with either human graft (OR 1.2; p = 0.007) or prosthetic graft (OR 1.56, p <0.001), while ultrasound (OR 1.65; p < 0.001) and arterial reconstruction (OR 1.64; p < 0.001) were significantly associated with antiplatelet use. Conclusions: In an international cohort of high-volume pancreas surgeons, significant variation in the use of AT following pancreatectomy with vascular reconstruction was observed. This variation was driven by geographical differences and the type of vascular reconstructions performed.
Veröffentlicht: 30. Juni 2025
Gesehen am 05.11.2025